KESESUAIAN PRINSIP PENGEMBANGAN RPP GURU BAHASA INDONESIA KELAS VIII SMP NEGERI SE-KECAMATAN SUMBAWA DENGAN PERMENDIKBUD NO. 22 TAHUN 2016 - Wiwik Surya Utami (Universitas Batanghari, 2022)
This study aims to describe the appropriateness of the principles of developing lesson plans for Indonesian language teachers for grade VIII at State Junior High Schools in Sumbawa with Permendikbud No. 22/2016. Teachers are guided by Permendikbud No. 22 of 2016. This research is a qualitative descriptive study. The subjects of this study were class VIII Indonesian teachers at State Junior High Schools in Sumbawa District. The object of this research is the learning implementation plan that has been designed by the teacher. The data were obtained through document analysis in the form of class VIII Indonesian language teacher lesson plans. The results showed that there were 2 teachers who were able to make lesson plans in accordance with the principles of developing lesson plans, namely teachers at SMPN 3 and teachers at SMPN 4. students encourage the enthusiasm for learning, finally the teacher of SMPN 5 is unable to formulate the principle of individual differences in students, the principle of centering on students, and the principle of applying information and communication technology.